Dimensional Stability and Characteristics of Modified Young Teak (Tectona grandis L.f.) Wood with PEG-1000 - Tomy Listyanto; Muhammad Navis Rofii; Keisuke Ando; Nobuaki Hattori (Masyarakat Peneliti Kayu Indonesia, 2015)
The aim of this study was to investigate the effect of wood modification with polyethylene glycol (PEG)-1000 at five concentrations to improve dimensional stability, drying, machining and finishing characteristics of young teak wood. A total of 12 samples for each treatment was prepared to measure an Anti Shrink Efficiency (ASE), as a parameter of dimensional stability and its drying characteristics. Six samples for each treatment were prepared to evaluate machining and finishing characteristics. PEG-1000 with five concentration levels of 20%, 30%, 40%, 50% and 60% were impregnated to modify the samples, except control. Afterward, all samples were kiln dried to gain 12% moisture content. ASE was determined by comparing shrinkage percentage of treated sample with those of untreated one. Warping and surface checks were measured as drying characteristics and machining test was conducted in accordance to ASTM D1666-2004. After coating with a nitrocellulose system, surface quality were evaluated by conducting cross-cut test (ASTM D3359), coin test, delamination test (SNI 01-5008.2-1999b) and glossyness test (SNI-06-6052-1999a). Result shows that dimensional stability of impregnated samples with concentration of 30 60% was successfully improved, with ASE of 52 62%. All treated samples demonstrated good drying characteristics and defect-free areas which were more than 90% under machining test. Surface evaluation by delamination test, glossyness test, and coin test indicated that all impregnated samples were well coated by a nitrocellulose system. However, only impregnated samples in concentration of 20% and 30% showed a good result in cross-cut test. Impregnation with PEG-1000 in concentration of 30% is recommended to modify young teak wood.